Digital Literacy and Competencies in Library and Information Science Education Students in Nnamdi Azikiwe University Awka - Okechukwu, Ngozi Njideka; Chika Jacinta Chinemerem; Nnatu Agatha Ujunwa (ILIN Institute Makassar, 2024)
This study delves into the digital literacy and competencies of Library and Information Science (LIS) students at Nnamdi Azikiwe University, Awka. Employing a quantitative approach with a descriptive survey design, data were gathered from 68 participants via a structured questionnaire on Google Survey. The questionnaire, using a 4-point Likert scale, covered demographic details, digital literacy levels, perceived curriculum effectiveness, impacts of pedagogical methods, identified barriers, and suggested improvement strategies. Analysis through descriptive statistics provided understandings into the digital proficiency of LIS students. The Kolmogorov-Smirnov and Shapiro-Wilk tests were used to assess normality. The Mann-Whitney U test examines differences between independent groups since the data violate normality assumptions and inform whether to accept or reject null hypotheses based on chosen significance levels. Results highlighted the expectations for LIS students to excel in digital libraries, archiving, system software, and communication. However, varying curriculum effectiveness was noted, influenced by accreditation standards and faculty expertise. Pedagogical methods such as hands-on learning and collaborative projects were found to enhance digital competencies, despite existing barriers like funding limitations and rigid curricula. The study advocates for curriculum enhancements, innovative pedagogy, and strategic interventions to bolster digital literacy in LIS programs.